The Effects of Religiousity, Pricing and Corporate Image on The Attitude and The Intention to Use Sharia Micro Financing - Zuliyanti Shabrina; Lilik Noor Yuliati; Megawati Simanjuntak (School of Business, IPB University (SB-IPB), 2018)
The Developing of Micro, Small and Medium Enterprises (MSMEs) in Indonesia could not be separated from the support of banking system in bank credit disbursement to MSMEs sector. Mandiri Sharia Bank (BSM) is one of the sharia banks that had disbursed sharia micro financing (micro credit). The objective of this research was to analyze the influence of religiosity, pricing and corporate image toward the attitude and the intention to use sharia micro financing. This research, hopefully, could give recommendations of marketing strategies to increase the number of debtors to use sharia micro financing (micro credit). This research used 150 respondents that had been chosen purposively with some criteria, such as entrepreneurs (prospective customers) who have a company in MSMEs sector but they have never experienced using sharia micro financing. The data were analyzed using SEM with SmartPLS3 software. This is a quantitative research using a descriptive approach. The data of respondents were collected by face-to-face interview using a questionnaire tool. The result showed that pricing and corporate image through the attitude provided significant influence on the intention to use sharia micro financing. Meanwhile, the religiosity and corporate image provide insignificant influence on the intention to use sharia micro financing. The fixed pricing and good corporate image would increase the attitude and the intention to use sharia micro financial services.Keywords: MSMEs, SEM, intention to use, pricing, sharia micro financing